Barriers to utilization of skilled birth attendance among post-natal women in a North Horr ward, Marsarbit County, Kenya: - Kofo, Kame; Matiang’i, Micah; Akolo, Maureen. (Edorium Journal of Maternal and Child Health, 2024)
Aims: The purpose of this study was to examine barriers to the utilization of skilled birth attendance among women in North Horr ward, Marsarbit County. Specific aims were to assess potential demographic, economic, sociocultural, and health facility barriers that facilitate home deliveries. Methods: A mixed methods approach was used. A survey questionnaire captured quantitative data from 306 women, while 15 semi-structured interviews were conducted to support the quantitative findings. Quantitative data were analyzed through descriptive and inferential statistics using Stata version 15, while qualitative data were analyzed thematically using NVIVO and presented in tabular form. Results: A total of 306 women participated (mean age=33 years). 92% (n=281) were married, 97% (n=297) had children, unemployment was 98% (n=300). Age, costs of transport, poor infrastructures, lack of money, and all health-related factors were significantly associated with place of delivery (p=0.0001). 50% (n=153) reported health facility as place of last delivery, 47% (n=144) delivered at home, though sociocultural factors like traditional birth attendant (TBA) availability (80% [n=123]) influenced the choice. The regression model showed no significant relationships for sociocultural barriers (p>0.05). Qualitative findings revealed financial constraints, sociocultural norms, and health infrastructure deficits as major barriers to skilled birth attendance utilization. Conclusion: Multifaceted barriers interact as barriers to the utilization of skilled birth attendance among women in North Horr ward, Marsarbit County. Initiatives aimed at improving skilled birth attendance utilization must judiciously tackle poverty, remoteness, inconsistent quality care and traditional mindsets.
A cross-sectional study